FORMS OF SUPPORT AND NEW HABITS AS K-POP FANS: IMPLICATIONS OF K-POP CULTURE ON THE LIFESTYLES OF FANS - Pricillia Haneyta Arisandi; Okta Wibowo, Tangguh; Janese Odelia Candra; Patricia Zarzycka; Dimas M Joseph (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
One of the most popular cultures today is the Korean culture. The phenomenon of the increasing popularity of Korean culture in the global sphere is referred to as the Korean Wave or Hallyu. The Korean Wave has brought international popularity to Korean dramas, food, fashion, makeup, and music. It has significantly increased the number of Korean fans around the world. In this context, research has been conducted to determine the impact of K-Pop media consumption on K-Pop fans. Specifically, the research focuses on the consumption patterns of products used by K-Pop idols. This research is expected to provide insight into the lifestyles of K-pop fans and how certain fans can influence the consumption of products used by their idols. The research is conducted using a descriptive phenomenological method, which uses a qualitative approach. This research highlights the changes in habits and new actions taken by K-pop fans as a form of support for their idols. Many K-pop fans are willing to spend a considerable amount of money to purchase K-pop goods and merchandise as a form of support. This research makes an important contribution to understanding how K-pop culture affects and shapes the lives of its fans.